A pragmatic evaluation of university student experience of remote digital learning during the COVID-19 pandemic, focusing on lessons learned for future practice. - Menna Brown; Alice E Hoon; Maisie Edwards; Shawn Shabu; Imannuella Okoronkwo; Philip M Newton (PLoS ONE, 2023)
The Covid-19 pandemic and subsequent national lockdowns resulted in drastic changes to the way that higher education was delivered. A mixed-methods research study was conducted to explore university students' perceptions of online learning during the 2020/21 academic year. Students from across all Welsh higher education institutions were invited to participate. First, a series of focus groups (n = 13) were conducted to explore students' experiences of online learning during the pandemic. Two were conducted in Welsh, the remaining eleven in English. Thematic analysis led researchers to develop eight key themes: Seeking the positives, Facilitators to learning, Barriers to learning, Lost sense of community, Let down by University, Workload, Assessment, and Health and well-being. These themes informed the design of a quantitative survey which was completed by 759 students. It was found that students were largely satisfied with the quality of online learning, however there were specific challenges associated with a lack of community, wellbeing concerns, and challenges with loneliness and isolation. Data from the focus groups and survey informed recommendations for practice in three key categories; teaching practice, institutional level recommendations, and student health and wellbeing considerations.